Dual orexin receptor antagonist in treatment of insomnia - Trajanovic, Nikola (Engrami, 2021)
A novel group of medications, dual orexin receptor antagonists, emerged as a competent group that challenges current first-line hypnotics. They have relatively infrequent and mostly well-tolerated side effects, primarily in the form of residual somnolence, fatigue and nightmares/disturbing dreams. The advantage over conventional hypnotics stems from the specifics of their target receptors, which translates into lack oftolerance after long term use and good safety profile. They are particularly favoured in some specific populations, including the elderly. Ongoing and future studies are set to explore their effect onselected conditions, such as addiction and psychiatric disorders, dementias, perimenopausal condition and circadian rhythm disorders, to name a few.
Keywords: Dual orexin receptor antagonis; sleep; hypnotics